2021
DOI: 10.1186/s12871-021-01375-w
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative pain management modalities employed in clinical trials for adult patients in LMIC; a systematic review

Abstract: Background Unrelieved postoperative pain afflicts millions each year in low and middle income countries (LMIC). Despite substantial advances in the study of pain, this area remains neglected. Current systematic review was designed to ascertain the types of clinical trials conducted in LMIC on postoperative pain management modalities over the last decade. Methods A comprehensive search was performed in June 2019 on PubMed, Cochrane Library, CINAHL P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Identifying ways to improve perioperative nursing is an urgent problem to be solved in clinical practice [19]. Research by foreign scholars has shown that the pain degree of adult patients after laparoscopic surgery is no less than that of knee replacement and thoracotomy [20,21]. Therefore, with the increasing number of laparoscopic surgeries, especially when the number of laparoscopic surgeries performed on children continues to rise, we must pay attention to the postoperative pain response.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying ways to improve perioperative nursing is an urgent problem to be solved in clinical practice [19]. Research by foreign scholars has shown that the pain degree of adult patients after laparoscopic surgery is no less than that of knee replacement and thoracotomy [20,21]. Therefore, with the increasing number of laparoscopic surgeries, especially when the number of laparoscopic surgeries performed on children continues to rise, we must pay attention to the postoperative pain response.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on pain care effectiveness, implications for patient recovery, and recognition of pain management as a human right have become issues central to the discourse around equitable healthcare [1][2][3]. Providing effective perioperative pain care is a challenge in Africa and around the world [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%